THE QUANTUM SHIFT: REIMAGINING ENTREPRENEURSHIP IN A NON-LINEAR WORLD - Victor Obasse; Taiye Adefemi Bamidele; Ifeanyi Ogbebor (Research Parks Publishers, 2026)
Entrepreneurship has often been framed as a linear pursuit grounded in prediction, planning, and controlled progression from idea to execution, yet this framing no longer aligns with the realities of contemporary environments shaped by uncertainty, interdependence, and rapid technological and societal change. This article develops a conceptual argument for a quantum shift in entrepreneurial thinking. The quantum shift describes a movement away from deterministic assumptions towards a more fluid, relational, and adaptive understanding of entrepreneurial activity, drawing on insights from complexity science, systems thinking, and digital transformation. Entrepreneurship is presented as a dynamic practice embedded within evolving networks of actors, technologies, and institutions, where opportunities emerge through interaction rather than through linear discovery. Illustrative cases demonstrate how non linear conditions reshape opportunity formation, strategic decision making, and value creation. The article proposes a conceptual framework that captures the essence of quantum entrepreneurship and outlines its implications for theory, practice, and policy.